Søren Kierkegaard : A Biography - Garff, Joakim (Book collections on Project MUSE., 2005)
Garff offers a detailed & incisive portrait of Sooren Kierkegaard, the philosopher, whose works had an enormous influence upon existentialism & postmodernism.